2022
DOI: 10.3389/fimmu.2022.1018393
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the B and T cell-mediated immune responses in patients with type 2 diabetes receiving mRNA or inactivated COVID-19 vaccines

Abstract: Acquiring protective immunity through vaccination is essential, especially for patients with type 2 diabetes who are vulnerable for adverse clinical outcomes during coronavirus disease 2019 (COVID-19) infection. Type 2 diabetes (T2D) is associated with immune dysfunction. Here, we evaluated the impact of T2D on the immunological responses induced by mRNA (BNT162b2) and inactivated (CoronaVac) vaccines, the two most commonly used COVID-19 vaccines. The study consisted of two parts. In Part 1, the sera titres of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
1
14
0
1
Order By: Relevance
“…Anti-RBD IgG antibodies are proved to be neutralizing against SARS-CoV-2 (39,40). In the present study, 98.2% (55/56) and 96.4% (54/56) of the non-DM subjects showed anti-N/S IgG positive and anti-RBD positive, respectively after a full vaccination with two doses at an interval of 2-4 weeks (Table 1 and Figure 2), which is in agreement with the results in the clinical trials (33,34). Thus, our data in the present study added more evidence that the inactivated COVID-19 vaccine efficiently elicited the non-neutralizing (anti-N) as well as neutralizing (anti-RBD) antibodies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Anti-RBD IgG antibodies are proved to be neutralizing against SARS-CoV-2 (39,40). In the present study, 98.2% (55/56) and 96.4% (54/56) of the non-DM subjects showed anti-N/S IgG positive and anti-RBD positive, respectively after a full vaccination with two doses at an interval of 2-4 weeks (Table 1 and Figure 2), which is in agreement with the results in the clinical trials (33,34). Thus, our data in the present study added more evidence that the inactivated COVID-19 vaccine efficiently elicited the non-neutralizing (anti-N) as well as neutralizing (anti-RBD) antibodies.…”
Section: Discussionsupporting
confidence: 92%
“…Considering that the positive rate of anti-RBD IgG was 97% in the non-T2DM subjects based on the results of clinical trials ( 33 , 34 ) and assumed 80% in the T2DM patients, we calculated that 46 patients per group would be required, with a power of 80% and a type I error rate of 0.05, by using a χ 2 -test. On the basis of an expected dropout of 10%, we planned to enroll 52 subjects per group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with an Israeli study on >342 healthcare workers with comorbidities given the BNT162b2 vaccine, which reported that diabetes was significantly associated with lower antibody concentrations (anti-RBD and Nabs) [23] . In contrast, Lee et al reported that T2D patients showed a reduction in CD4+ T-helper-1 (Th1) differentiation following their first dose of BNT162b2 vaccine [24] . However, this initial defect was rectified by the second dose, resulting in levels of CD4+ memory T-cells and CD8+ T cells, anti-RBD IgG, and Nabs that were comparable to healthy individuals at 3–6 months after vaccination [24] .…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, Lee et al reported that T2D patients showed a reduction in CD4+ T-helper-1 (Th1) differentiation following their first dose of BNT162b2 vaccine [24] . However, this initial defect was rectified by the second dose, resulting in levels of CD4+ memory T-cells and CD8+ T cells, anti-RBD IgG, and Nabs that were comparable to healthy individuals at 3–6 months after vaccination [24] . In one recent Kuwaiti study, both T2D ( n = 81) and non-diabetic individuals ( n = 181) elicited strong immune responses to SARS-CoV-2 BNT162b2 mRNA vaccine; nonetheless, lower levels were seen in people with diabetes, suggesting that continuous monitoring of the antibody levels might be a good indicator to guide personalized needs for further booster shots to maintain adaptive immunity [25] .…”
Section: Discussionmentioning
confidence: 95%